Trajectory Generation Module Design for Robot Manipulators - Souza, Gabriel; Dutra, Gustavo; Zanlucchi, Jose Jean-Paul (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
Following the technology demands created by Industry 4.0, robot manipulator popularity has increased significantly. One of the crucial aspects on its application is the calculation of a suitable and eﬃcient trajectory to the objective states, converting action plans into control references for the robot system controller. This paper presents the development of a generic trajectory planner, were simple and generic techniques are favored for maintenance and portability, thus it was created as an independent module to be included as part of a modular generic architecture that wields those advantages. It’s composed of two nested processes, the first responsible for generating a point-by-point trajectory and the following, an internal process responsible for calculating a satisfactory set of controller references to achieve the generated trajectory point, using a numerical optimization approach. The explored optimization technique is based on using the robots Direct Geometric Model (DGM) and the Jacobian pseudo-inverse, to iterate searching for local minima in the error surface, using the pseudo-inverse to direct the actuator references towards a solution. A didactic example is presented to clarify on the required information and steps, and to observe parameter eﬀects on behavior and results. A discussion of restrictions and optimized solutions is also carried along the text.